A new species and records of Paraphloeostiba Steel, 1860 (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2025)
Taxonomic and faunistic data for 12 species of the genus Paraphloeostiba Steel, 1860 is presented. A new species is described and illustrated: P. subopacoides sp. nov. (China: Yunnan). Images of the habitus of P. formosana Shavrin & Smetana, 2016 and P. similis Steel, 1960 are presented. First records are provided for the following seven species: P. alutacea (Cameron, 1941) from Vietnam and Negros Island (Philippines), P. brevicula Shavrin, 2024 and P. rhopalocera (Cameron, 1928) from Solomon Islands, P. formosana Shavrin & Smetana, 2016 from Kerala (India) and Vietnam, P. gayndahensis (McLeay, 1873) from Russia (Maritime Province), Taiwan and Solomon Islands, and P. similis Steel, 1960 from Malaysia.